2009
DOI: 10.1111/j.1471-4159.2009.06466.x
|View full text |Cite
|
Sign up to set email alerts
|

Rab3a interacting molecule (RIM) and the tethering of pre‐synaptic transmitter release site‐associated CaV2.2 calcium channels

Abstract: Biochemical and physiological evidence suggest that pre-synaptic calcium channels are attached to the transmitter release site within the active zone by a molecular tether. A recent study has proposed that 'Rab3a Interacting Molecule' (RIM) serves as the tether for CaV2.1 channels in mouse brain, based in part on biochemical co-immunoprecipitation (co-IP) using a monoclonal antibody, mRIM. We previously argued against this idea for CaV2.2 calcium channel at chick synapses based on experiments using a different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 32 publications
(52 reference statements)
4
30
0
Order By: Relevance
“…These have been described in detail (Juhaszova et al, 2000; Wong and Stanley, 2010; Gardezi et al, 2013; Wong et al, 2013). Key preparation buffers were: homogenization buffer (HB), 0.32 M sucrose, 10 mM HEPES, 2 mM EDTA, pH 7.4; HEPES lysis buffer, 50 mM HEPES, 2 mM EDTA, pH 7.4; and modified radioimmunoprecipitation assay solubilization buffer (RIPA), 50 mM Tris-HCl, 150 mM NaCl, 1% NP-40, 0.5% Na + deoxycholate, 1 mM EDTA, pH 8.4)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These have been described in detail (Juhaszova et al, 2000; Wong and Stanley, 2010; Gardezi et al, 2013; Wong et al, 2013). Key preparation buffers were: homogenization buffer (HB), 0.32 M sucrose, 10 mM HEPES, 2 mM EDTA, pH 7.4; HEPES lysis buffer, 50 mM HEPES, 2 mM EDTA, pH 7.4; and modified radioimmunoprecipitation assay solubilization buffer (RIPA), 50 mM Tris-HCl, 150 mM NaCl, 1% NP-40, 0.5% Na + deoxycholate, 1 mM EDTA, pH 8.4)…”
Section: Methodsmentioning
confidence: 99%
“…Our quantitative immunocytochemical analysis [Intensity Correlation Analysis, (Li et al, 2004)] supported the idea that that CaV2.2 and RIM co-vary at presynaptic transmitter release sites (Khanna et al, 2006a). However, the failure to detect a CaV2.2-RIM complex by biochemical analysis suggests that these proteins are parts of two independent, but possibly transiently interacting, complexes (Khanna et al, 2006a; Wong and Stanley, 2010; Wong et al, 2013) and is at odds with the current tether molecular model. …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The interaction seems to occur via a RIM PDZ motif that binds the Ca v 2 channel C-terminus; in mouse, targeted deletion of the RIM PDZ disrupts proper channel localization and synaptic transmission, and a direct physical interaction was observed between this motif and the channel C-terminus via yeast-two hybrid and NMR spectroscopy assays. However, a similar interaction was not observed in the chick synapse using co-immunoprecipitation (Khanna et al, 2006; Wong and Stanley, 2010), and a separate study found that RIM tethering of Ca v 2 channels requires the Ca v β subunit to serve as an intermediary between the two proteins (Kiyonaka et al, 2007). Recently, evidence has emerged that Ca v 2 channel pre-synaptic scaffolding undergoes a developmental switch in Drosophila , where different mRNA splice isoforms of the vesicle priming protein UNC-13 interact with distinct scaffolding proteins for either microdomain tethering in immature synapses (i.e., with Syd-1 and Liprin-α), or nanodomain tethering in mature synapses (i.e., with Bruchpilot and RIM-associated protein complexes) (Böhme et al, 2016).…”
Section: Cav Channel Physiology In Basal Metazoansmentioning
confidence: 77%
“…It was shown that Rim Binding Proteins directly interact with Ca v 2.2 channels (and possibly with Ca v 2.1 channels), suggesting a molecular link between voltage-gated Ca 2+ channels and Rim proteins [ 116 ] . Whereas biochemical studies using synapstosome membranes failed to demonstrate the existence of a Ca v 2.2/Rim complex [ 117 ] , in vitro studies indicate a direct interaction of Rim-1 with the synprint site of Ca v 2.2 channels [ 109 ] as well as with SNAP-25 and synaptotagmin-1 via the C2 domains in a Ca 2+ -dependent manner. At low Ca 2+ concentrations Rim-1 thus preferentially binds SNAP-25 whereas an increase in Ca 2+ concentration (>75 m M) favors its interaction with synaptotagmin-1 [ 109 ] .…”
Section: Modulation By Rim-1mentioning
confidence: 95%